Orfeo y los misterios griegos - García Álvarez, César, 1970- (2023)
El tema central de esta investigación es Orfeo y los Misterios Griegos. El autor analiza el Orfeo doctrinal, después pasa a dramatizar imaginativamente el interior de un Misterio.
The central theme of this research is Orpheus and the Greek Mysteries. The author analyzes the doctrinal Orpheus, then goes on to imaginatively dramatize the interior of a Mystery.
Keywords: Orfeo; Civilización griega